Women in Nuclear Security: The United Arab Emirates Story - Mohamad Z Zineddin (International Journal of Nuclear Security, 2025)
Historically in the United Arab Emirates, security personnel stationed at nuclear sites were typically men with military or policing backgrounds. Although these groups bring important, transferrable skills and experience to the nuclear security mission, some Emirati stakeholders recognize the increased benefit of a greater diversity of voices and backgrounds within the nuclear security team hierarchy. By recruiting from a wider range of disciplines and encouraging gender diversity, the security team could develop broader insight into security challenges, and a greater variety of perspectives could bring forth more innovative solutions. When aligning a diverse, multinational workforce with a common mission, all members of a security organization must fundamentally change their individual approaches to the work; the entire staff must be on the same page. This can be particularly challenging for some people who find it difficult to transition from a framework of beliefs because of past experiences based on prescriptive, exclusionary, hierarchical thought. Also, national cultural values are learned early, held deeply, and change slowly over the course of generations, and inherent biases rooted in these values can create barriers to the collective progress of a team. Creating a more open, diverse, and transparent culture for the team by accepting a unique, egalitarian, professional nuclear security culture that all members adhere to can be a challenging task for some. In this article, I share my experiences related to professional roadblocks, personal challenges, and lessons learned, particularly those regarding the empowerment of women in science and engineering, while developing and establishing the United Arab Emirates nuclear security program. I also discuss the support (and underrepresentation) of women, including those currently in critical leadership positions, and their careers in nuclear security.
Keywords: Nuclear Security; Women in Nuclear; IAEA; WINS; UAE; Barakah NPP